Experimental Research on Vibration Reduction of Cantilever Structure in High-Temperature Environments - Di Jia; Fuhao Peng; Tao Zhou; Xueren Wang; Qingliang Lu; Yiwan Wu (Shock and Vibration)
To reduce the vibration of a cantilever steel plate in high-temperature environments (25°C–500°C), a new composite structure with entangled metallic wire material (EMWM) core was proposed. The damping performance of the EMWM under different temperatures was investigated. The results show that when the temperature does not exceed 260°C, the damping property of the EMWM is not affected by temperature. When the temperature exceeds 260°C, the damping property of the EMWM decreases with the increase of temperature. A thermal-vibration joint test system was set up to verify the energy dissipation mechanism of the composite structure with EMWM core and to research the effect of vibration reduction under different temperatures. The displacement deviation between the baseplate (steel plate) and constraining plate was sufficient to cause frictional energy dissipation of the EMWM core. The thermal-vibration joint test results indicated that the EMWM core had a positive impact on the damping properties of the cantilever structure. Adding EMWM core and constraining plate can significantly increase the damping ratio and reduces the vibration of the cantilever structures under different temperatures. This research is helpful to control the structural vibrations of cantilever structures in high-temperature environments.